Mycobacterium genavense Infections in Immunocompromised Patients Without HIV: Case Series of Solid Organ Transplant Patients and Literature Review. (30th September 2022) - Baldolli, Aurélie; Chocron, Richard; Dargère, Sylvie; Michon, Jocelyn; Daurel, Claire; Thuillier-Lecouf, Angélique; Verdon, Renaud
Abstract: Background: Mycobacterium genavense infection is rare and can occur in immunocompromised patients without human immunodeficiency virus (HIV). Methods: We describe 2 cases of M genavense infection in solid organ transplant (SOT) recipients, and we performed a literature review of immunocompromised patients without HIV. Results: Fifty-two cases are reported. Predisposing factors were receipt of SOT (40.4%) and autoimmune disease (36.5%). Infection was disseminated in 86.5% of cases. Organs involved were lymph nodes (72.3%), gastrointestinal tract (56.5%), lung (35.5%), and bone marrow (28.8%). Most patients were treated with at least 3 antimycobacterial agents (98%), with a clinical cure achieved in 54.9%. In multivariate analysis, lack for cure was associated with age of the time infection (odds ratio [OR], 15.81 [95% confidence interval CI, 2.92–152.93]; P = .011) and positive bone marrow culture (OR, 1.05 [95% CI, 1.01–1.12]; P = .042). Conclusions: Mycobacterium genavense infection is a rare and generally disseminated disease with a poor prognosis. Optimal treatment regimen and its duration remain to be defined.